(untitled) - Norris, Roy (London, 2014)
Focuses on thorough preparation for the Cambridge English: Advanced (CAE) exam. In this title, the end of unit Review sections and the practice exam papers develop exam confidence. It comes with audio and an access code to Macmillan Practice Online (MPO) providing students with more material for exam preparation. It is a 'With Key' version.
Keywords: English language,Tiếng Anh; Examination,Kỳ thi